Elementary School Teachers’ Perceptions in Balikpapan on the Dynamics of Curriculum Changes in Indonesia - Reza June Sidiq; Khusnul Khatimah; Rani Herning Puspita (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study explores the perceptions of elementary school teachers in Balikpapan regarding the ongoing changes in Indonesia’s national curriculum, focusing on the shift from the 2013 Curriculum to the Merdeka Curriculum. Frequent changes in the national curriculum have led to confusion and varied responses among educators, particularly in terms of instructional adaptation and professional readiness. The purpose of this research is to understand how teachers perceive these changes, what challenges they face in implementing the new curriculum, and the extent to which they feel supported through training and resources. This study employed a qualitative descriptive design, using semi-structured interviews and classroom observations to collect data from nine teachers selected through purposive sampling. Thematic analysis was used to identify patterns and develop categories based on participant responses. Findings reveal that while teachers generally view the Merdeka Curriculum positively emphasizing its flexibility, student-centered learning, and relevance to current needs they also report significant challenges related to limited training, unclear implementation guidelines, and mismatched support systems. These results contribute to a deeper understanding of how educational reforms are received at the grassroots level and underscore the importance of teacher involvement, practical training, and contextualized guidance in successful curriculum implementation.